Enhancing Cyber Security in College Student Ideological Education Platforms through Blockchain Integration - Zhang, Yuan; Wang, Fei (International Journal of Social Sciences and Public Administration, 2024)
This paper investigates the optimization of online ideological and political education platforms in universities, utilizing systematic thinking based on the principles of systematicity, wholeness, dynamism, and orderliness. We aim to align these platforms with the development trends of the network era and achieve efficient and optimized development. The integration of blockchain technology into these platforms is proposed to enhance cyber security, secure coordination, and collaboration in a distributed system. This study explores the theoretical and practical significance of blockchain in ideological education and addresses the challenges and strategies for optimizing these platforms.